A point mutation in the γ(2) subunit of γ-aminobutyric acid type A receptors results in altered benzodiazepine binding site specificity - Buhr, Andreas (The National Academy of Sciences of the USA, 1997)
Benzodiazepines allosterically modulate γ-aminobutyric acid (GABA) evoked chloride currents of γ-aminobutyric acid type A (GABA(A)) receptors. Coexpression of either rat γ(2) or γ(3), in combination with α(1) and β(2) subunits, results both in receptors displaying high [(3)H]Ro 15-1788 affinity. However, receptors containing a γ(3) subunit display a 178-fold reduced affinity to zolpidem as compared with γ(2)-containing receptors. Eight chimeras between γ(2) and γ(3) were constructed followed by nine different point mutations in γ(2), each to the homologous amino acid residue found in γ(3). Chimeric or mutant γ subunits were coexpressed with α(1) and β(2) in human embryonic kidney 293 cells to localize amino acid residues responsible for the reduced zolpidem affinity. Substitution of a methionine-to-leucine at position 130 of γ(2) (γ(2)M130L) resulted in a 51-fold reduction in zolpidem affinity whereas the affinity to [(3)H]Ro 15-1788 remained unchanged. The affinity for diazepam was only decreased by about 2-fold. The same mutation resulted in a 9-fold increase in Cl 218872 affinity. A second mutation (γ(2)M57I) was found to reduce zolpidem affinity by about 4-fold. Wild-type and γ(2)M130L-containing receptors were functionally expressed in Xenopus oocytes. Upon mutation allosteric coupling between agonist and modulatory sites is preserved. Dose–response curves for zolpidem and for diazepam showed that the zolpidem but not the diazepam apparent affinity is drastically reduced. The apparent GABA affinity is not significantly affected by the γ(2)M130L mutation. The identified amino acid residues may define part of the benzodiazepine binding pocket of GABA(A) receptors. As the modulatory site in the GABA(A) receptor is homologous to the GABA site, and to all agonist sites of related receptors, γ(2)M130 may either point to a homologous region important for agonist binding in all receptors or define a new region not underlying this principle.